Effectiveness of Mirror Therapy on Improving Motor Function and Activities of Daily Living in Post-Stroke Patients with Hemiparesis - Wirmando, Wirmando; Sampe, Sr. Anita; Tangdiembon, Lilianti; Tarrapa, Lulu Wananda; Hogen, Lusius Sandiago; Saranga', Jenita Laurensia; Makagiansar, Shanti Pricillia T; Garesso, Francilia Petra Tonapa (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
One of the major impacts of stroke is chronic motor deficits or hemiparesis, with approximately 80% of patients potentially experiencing permanent disability that leads to reduced independence in performing activities of daily living (ADL). Optimal rehabilitation is essential to prevent these long-term consequences. This study aimed to analyze the effectiveness of mirror therapy in improving motor function and ADL performance among post-stroke patients with hemiparesis. The study employed a pre-test and post-test equivalent control group design with a total of 60 respondents selected using consecutive sampling and divided into intervention and control groups. The intervention group received mirror therapy combined with conventional rehabilitation based on the Bonner protocol, whereas the control group received only conventional therapy. Motor function was assessed using a handgrip dynamometer, and ADL was evaluated using the Barthel Index. Results showed that most respondents were over 50 years old (86%), male (60%), and diagnosed with non-hemorrhagic stroke (93%). Statistical analysis revealed significant improvements in motor function in both the intervention group (p=0.000) and the control group (p=0.001). Significant improvements in ADL were also observed in the intervention group (p=0.000) and the control group (p=0.000). Comparison between groups demonstrated significant differences in motor function (p=0.004) and ADL (p=0.000). These findings indicate that mirror therapy is effective in enhancing motor function and ADL performance in post-stroke patients with hemiparesis. Therefore, mirror therapy is recommended to be incorporated into physiotherapy standard operating procedures for post-stroke rehabilitation.